Development of activeness and independence in students of senior grades by imparting new knowledge of humanities subjects - Rajackas, V. (Psichologija, 1963)
Bringing up a tomorrow’s communist person, a major part is played by humanities subjects. Therefore, along with restructuring the work of the whole school, it is essential to improve teaching of these subjects assuring that they will facilitate preparation for life, work and active participation in building of communism. This article dedicated to the analysis of imparting new knowledge in history and literature lessons in senior grades pays major attention to the development of students’ independence, activeness, deeper assimilation of knowledge and the methods up till now not enough applied in school practice, i.e. individual work of students with course books and other printed sources, application of various methods during the lesson to convey new material; the attention in the article is also drawn to the significance of students’ papers and vocal communication, organization of independent work of students by using other methods. By referring to experimental material, it is shown that students achieve creditable results by individual work with course book and other printed sources. The article analyses several methods of work with a course book. Concrete examples are analyzed to demonstrate how the previously studied material is revised and consolidated by conveying new one, how it is linked with the newly covered. This helps students to learn the lesson and avoid individual examination and assessment of knowledge at the end of the lesson. In such way, the template four-element structure of a lesson is altered and the best ideas and best practice of Lipeck district and other best schools are implemented. Through creative conveyance of new material in History and Literature lessons, all students can be active. For this purpose it is necessary to apply all methods known to school practice and the pedagogy science in such way as to ensure active and attentive work of all students and, in proper conditions, ensure their individual attempts to gain new information. When students are engaged in active work, their involvement in a subject increases, interests develop, they assimilate and consolidate the material during the lesson and all this cultivates their positive attitude towards individual subjects and learning in general.